DETERMINAN HOLDING PERIOD JAKARTA ISLAMIC INDEX - Fathani, Nurul Fathani; Oktaviana, Ulfi Kartika (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2018)
Market of financial capital is a good media to distribute the finance from the investors to the companies that need it. The investors give an investation to get a profit in the shape of capital gain or dividend. They can optimize the profit by deciding the golden time to buy or sell the investation. One of the ways to decide when the golden time comes is by looking at the holding period of the investation. A high holding period is showing a good condition of the investation because the investors will hold it when they get the profit optimally. That is also done in the contrary. This research is done to know the impact of market value, bid ask spread, and dividend payout ratio to the holding period. The samples of this research are all of the companies in Jakarta Islamic Index (JII) around 2014-2016 in sum thirteen in which the samples are taken by using purposive sampling. The data is a secular data that is got by the daily and annual report from the research object. Then, the data analysis process that is used is a regressive analysis of panel data with Eviews 9 program. The result of this research shows that, simultaneously, the variable of market value, bid ask spread, and dividend payout ratio is significantly influencing the holding period. Partially, the variable of dividend payout ratio has a positive influence to the holding period significantly, while for the variable of market value, variant return, and bid ask spread do not have a significant influence to the holding period.